2023
DOI: 10.1109/rbme.2021.3121480
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Printed Temperature Sensors: Short Review on Latest Advances for Biomedical Applications

Abstract: The rapid growth in wearable biosensing devices is driven by the strong desire to monitor the human health data and to predict the symptoms of chronic diseases at an early stage. Different sensors are developed for continuous monitoring of various biomarkers through wearable and implantable sensing patches. Temperature sensor has proved to be an important physiological parameter amongst the various wearable biosensing patches. This paper highlights the recent progresses made in printing of functional nanomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 177 publications
(297 reference statements)
0
25
0
Order By: Relevance
“…The strong desire to monitor human health data is driving the rapid growth of wearable biosensing technologies. Among the different wearable biosensing devices, temperature measurement has proven to be an important physiological parameter [29]. The accurate and continuous measurement of the human core body temperature by a wearable device is of great significance for human healthcare and disease monitoring [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The strong desire to monitor human health data is driving the rapid growth of wearable biosensing technologies. Among the different wearable biosensing devices, temperature measurement has proven to be an important physiological parameter [29]. The accurate and continuous measurement of the human core body temperature by a wearable device is of great significance for human healthcare and disease monitoring [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…3D printing can also be used to print certain electronics to be added to the drug delivery devices. 3D printed electronics such as biological sensors which can measure glucose, temperature and sweat can be printed [68][69][70]. The desired design can also be directly printed into or onto the device [71].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…14 It is important to thoroughly evaluate the potential risk of PMMA for long-term skin contact, as it may not be safe as other biocompatible polymers like poly(dimethyl siloxane). 3,15 In particular, using PMMA with molecular weights (MWs) ranging from 3,000 to 50,000 g/mol is attractive as a material for constructing WDs. [16][17][18] Nevertheless, most of the biological effects assessments of PMMA have been performed in conjunction with other compounds, and the MW has been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, Trinh et al reported the use of a PMMA‐based microfluidic device (2.4 mg of PMMA/cm 2 ) for sensing applications 14 . It is important to thoroughly evaluate the potential risk of PMMA for long‐term skin contact, as it may not be safe as other biocompatible polymers like poly(dimethyl siloxane) 3,15 . In particular, using PMMA with molecular weights (MWs) ranging from 3,000 to 50,000 g/mol is attractive as a material for constructing WDs 16–18 .…”
Section: Introductionmentioning
confidence: 99%